Optical photon reassignment with increased axial resolution by structured illumination. (22nd November 2016) - Roth, Stephan; Heintzmann, Rainer
Abstract: Fluorescent microscopy methods linked to the reassignment principle as image scanning microscopy (ISM), re-scan confocal (RSC), optical photon reassignment (OPRA) and instant structured illumination microscopy (iSIM) have the potential to replace confocal microscopy as the standard microscopy technique. Photon reassignment methods are known to link the most important properties in biological imaging as resolution, sensitivity, imaging speed and combinability with fluorophores in an elegant way. On the example of OPRA, we show how this method could be easily extended to the third dimension. If OPRA is used in combination with a structured illumination pattern the sectioning ability can be improved while maintaining the very high signal intensity. We present a detailed analysis about the imaging properties of OPRA in three dimensions and show experimental results on biological samples.